Estimacion de la radiacion solar global sobre España a partir de datos Meteosat usando un modelo físico - Rojas, Joel (2021)
Solar radiation over Spain has been estimated from METEOSAT images, using a two-way physical method. The results for any cloud cover condition are compared with measurements on the ground made by 6 Spanish meteorological stations. The precision of the method on a test file (1110 hourly measurements for 5 days of March, June, September and December 1993), in terms of mean and square error is 6.3 W / m2 and 87.9 W / m2 (18.2%) respectively. This method will be improved within an operational scheme established for a systematic evaluation of forest fires on the Iberian Peninsula.